Precancerous cervical lesion and associated factors among HIV-infected women on ART in Amhara Regional State, Ethiopia: A hospital-based cross-sectional study - Belayneh, Tadesse (Int J Health Sci (Qassim), 2019)
OBJECTIVE: Cervical cancer, which is caused by human papillomavirus, is one of the common cancers in women worldwide. The proportion of precancerous cervical lesion among HIV-infected women has not been investigated yet in this study area. The aim of this study was to determine the proportion of precancerous cervical lesion and associated factors among HIV-infected women on ART in Woldia and Dessie Hospitals, Amhara Regional State, Ethiopia. METHODS: A hospital-based cross-sectional study was conducted on 284 HIV patients. Data were collected using a structured questionnaire and visual inspection. Pap smear test was employed for confirmation of cancer. Descriptive statistics were used to summarize findings. A logistic regression model was considered to identify predictors of precancerous cervical lesions. Those variables with P < 0.05 at a 95% confidence interval were considered as statistically significant. RESULTS: The overall proportion of precancerous lesion among HIV-infected women in this study was 9.9%. Among HIV-infected women age greater than 30 years old, single in marital status, commercial sex worker, had any other sexually transmitted infection, more than one sexual partner, more than two children and with vaginal wall abnormality were factors associated with the occurrence of precancerous cervical lesion. CONCLUSION: The proportion of precancerous cervical lesion among HIV-infected women was low compared to some previous studies conducted among HIV-infected women in Ethiopia. Therefore, regular screening of HIV-infected women for precancerous cervical lesion is very important by giving especial consideration to identified associated factors.